An Actuator Fault Detection and Reconstruction Scheme for Hex-Rotor Unmanned Aerial Vehicle - Wang, Rijun; Zhao, Changjun; Bai, Yue; Du, Wenhua; Wang, Junyuan (IEEE access, 2019)
The detection and the reconstruction of actuator faults in a flight control system are crucial to avoid negative impacts on the aircraft itself, as well as human and environmental systems. In this paper, an actuator fault detection and reconstruction scheme based on fault classification for the hex-rotor unmanned aerial vehicle are designed. First, the fault type of actuator is analyzed and classified, then an actuator fault model is established based on multiple fault classification. Second, a fault detection and reconstruction (FDR) scheme for the hex-rotor unmanned aerial vehicle is proposed. In the proposed scheme, a fault observer group based on an extended Kalman filter (EKF) is designed for fault detection and isolation, and the flight state feedback required by the fault observer group is provided by the multi-sensor navigation unit (MSNU). Then, a fault reconstruction algorithm of the actuator is proposed by using the output of the fault observer group. The designed FDR system is applied to hex-rotor unmanned aerial vehicle prototype for its evaluation. The simulation results show that the proposed design is capable of fault detection and the reconstruction of actuator faults, and the actual flight verifies the effectiveness of the proposed methods.